4, 4′‐Bipyridine‐1, 1′‐diium acetylenedicarboxylate: a new member of the (H2bipy)[Cu(ox)2] (bipy is 4, 4′‐bipyridine and ox is oxalate) family. Issue 5 (2nd April 2015) - Chen, Xiaocui; Wang, Yue; Han, Shumin; Wei, Yongju; Wang, Ruiyao
<x xml:space="preserve">Abstract</x> 4, 4′‐Bipyridine‐1, 1′‐diium (H2bipy) acetylenedicarboxylate, C10H12N22+·C4O42−, (1), is a new member of a family of related structures with similar unit‐cell parameters. The structures in this family reported previously [Chen et al. (2012). CrystEngComm, 14, 6400–6403] are (H2bipy)[Cu(ox)2] (ox is oxalate), (2), (H2bipy)[NaH(ox)2], (3), and (H2bipy)[H2(ox)2], (4). Compound (1) has a one‐dimensional structure, in which H2bipy2+ cations and acetylenedicarboxylate (ADC2−) anions are linked through a typical supramolecular synthon, i.e.R22(7), and form linear `–cation–anion–' ribbons. Through an array of nonclassical C—H...O hydrogen bonds, adjacent ribbons interact to give two‐dimensional sheets. These sheets stack to form a layered structure viaπ–π interactions between the H2bipy2+ cations of neighbouring layers. The supramolecular isostructurality of compounds (1)–(4) is ascribed to the synergistic effect of multiple interactions in these structures. The balanced strong and weak intermolecular interactions stabilizing this structure type include strong charge‐assisted N—H...O hydrogen bonds, C—H...O contacts and π–π interactions.